FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMERIKSAAN PAYUDARA SENDIRI SEBAGAI METODE DETEKSI DINI KANKER PAYUDARA DI PUSKESMAS TEGINENENG KABUPATEN PESAWARAN - Bajuri, Annisa Nur Oktavia; Sari, Ratna Dewi Puspita; Soleha, Tri Umiana (Medula, 2024)
Breast cancer is the uncontrolled growth of cells in the lobules, ductus and supporting tissue of the breast that surrounds them. An examination for early detection of breast cancer is breast self-examination (BSE) which can reduce the mortality rate by 25-30%. Pesawaran District in 2018 had a coverage of the PTM indicator for BSE examination of 16,20%, with the highest achievement at the Gedong Tataan Community Health Center of 27,83% and the lowest in Tegineneng Community Health Center of 4,17%. This research was conducted to determine the factors associated with BSE behavior in women of childbearing age (WUS) in Tegineneng Community Health Center, Pesawaran Regency. The research used an analytical observational method with a cross sectional approach. The sampling technique was cluster sampling. Data was collected using a questionnaire and analyzed with chi-square test. The results showed that there was a significant correlation between knowledge (p-value 0.003) and media information (p-value 0.000) on BSE behavior. There was a significant relationship between knowledge and information media on BSE behavior. Meanwhile, there was no significant relationship between age, motivation, and the role of health workers on BSE behavior.